ANALISIS KESESUAIAN PENGGUNAAN LAHAN TERHADAP POLA RUANG DI DAERAH ALIRAN SUNGAI BIALO - Andang Suryana Soma (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2021)
This research aims to analyze the land use and identify the suitability of the land use plan of space in Bialo Watersheds and determine the direction of land use if there is a mismatch between the land use with the regional plan in Bialo watersheds. The data were collected in primary data was the land use and secondary data of regional plan. The data were analyzed with interpretation, test accuracy, and conformity determination for land use overlay with the plan space. Based on the analysis of land-use suitability with the plan space, a land-use plan is acquired that fits the area of 87.80% and is not following 12.20%. Use of the referral in the form of reboisation, the village forests, agroforestry, multi-purpose tree species (MPTS) on dry land forest land use, agricultural secondary dry land, settlements. Planting cover crops and soil reinforcement terrace on paddy fields and natural succession on land use scrub.